ChatGPT and responsible student education - Gałat, Wioleta (Zielona Góra: Faculty of Economics and Management Press)
The article aims to identify the significance of ChatGPT in shaping key skills and competencies among students, framed within the concept of responsible education. Responsible education is defined as enabling young people to actively engage in the labour market, create their career paths, and adapt to changing conditions. The study achieves its aim through a literature review identifying relevant skills and competencies for responsible education, followed by a survey conducted among students to draw critical conclusions. Additionally, an original assessment of ChatGPT`s potential in responsible education is provided, along with educational recommendations.
Keywords: ChatGPT; responsible education; education